Protected: Reverse engineering injury mechanism and the consequences of forward engineering - Charniga, B. (EWF Scientific Magazine, 2018)
Squatting under and receiving a heavy barbell at high speed without negative consequences; disproves the common myth ligaments and joints are susceptible to injury from fast, large range of motion exercises. Five previous essays explored the possibility of a concept of reverse engineering as a means to ascertain the etiology of common sport injuries by analyzing circumstances in weightlifting, where one would logically expect an injury to occur; but no injury is manifest. A reverse engineering analysis begins with the 'why' someone is not injured under circumstances an injury should certainly occur. Insight from this analysis is applied to determine why serious lower extremity injuries in non - contact running, jumping and so forth, should not only not occur; but should not be commonplace in the USA. In essence, the logic of reverse engineering injury centers around practical experiences with already known outcomes. Whereas, for want of a better term, 'forward engineering' begins and ends with guesses founded on false truisms. A number of these false truisms underpinning forward engineering have been have been elucidated in previous essays such as: "The demands placed on the muscles and ligaments of the knee joint during deep squats are severe. A much safer alternative would be the half squat exercise." Luttgens, 2002. The hurdlers stretch: "This abnormal stretch places high stresses on the medial structures of the knee joint, which may lead to ligament damage and eventual instability." Luttgens, Hamilton, 2002 Even though these false truisms and many others of the same vein have appeared in respected Kinesiology books, medical texts, journals and the like, for many years; there is no validity offered and no attempt is made to establish proof of such claims. They point to the hazards created by forward engineering, i.e., predicting injury or susceptibility because of assumptions based on the false belief stretching ligaments or bending a a certain way is dangerous. Why call the spread of the forward engineering ideas a 'hazard'? After many years of print, word of mouth, instructional video and so forth, these ideas become so ingrained in the collective conscience, they are not questioned. Or, in the words of Thomas Paine "A long habit of not thinking a thing wrong gives it a superficial appearance of being right". These ideas have gained such universal acceptance in the USA that professional teams, university athletics, high schools, elementary schools, fitness magazines, exercise classes are all following the same exercise protocols to restrict knee bends to movement at the hip and knee with minimal movement of the ankle. Furthermore, ankle joints are routinely supported with braces, and/or taped to restrict movement and even feet to shoes beginning already in high school football. However, the problems created by unsubstantiated forward engineering claims such as stretching ligaments will lead to instability, are incalculable. Enumerable laymen, professional, academic and medical alike, who hear or read of such false ideas; accept them as fact and pass on to others through word of mouth, writings, videos and so forth over a period of many years. Consequently, assuming these ideas are correct the majority never stop to question their veracity.